1988
DOI: 10.2307/1911077
|View full text |Cite
|
Sign up to set email alerts
|

On the Theory of Infinitely Repeated Games with Discounting

Abstract: This paper presents a systematic framework for studying infinitely repeated games with discounting, focussing on pure strategy (subgame) perfect equilibria. It introduces a number of concepts which organize the theory in a natural way. These include the idea of an optimal penal code, and the related notions of simple penal codes and simple stratea profiles. I view a strategy profile as a rule specifying an initial path (i.e., an infinite stream of one-period action profiles), and punishments (also paths, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
604
0
8

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,062 publications
(618 citation statements)
references
References 7 publications
6
604
0
8
Order By: Relevance
“…Abreu (1988) proves that simple strategy pro…les are simple not only because of their de…n-ition but also because it is easy to check whether they are subgame perfect equilibria. According to his Proposition 1 (p. 391), only one-shot deviations need be checked to ensure subgame perfection, where a one-shot deviation from a strategy consists of a single period deviation followed by sticking to the strategy afterwards.…”
Section: De…nitionmentioning
confidence: 94%
See 1 more Smart Citation
“…Abreu (1988) proves that simple strategy pro…les are simple not only because of their de…n-ition but also because it is easy to check whether they are subgame perfect equilibria. According to his Proposition 1 (p. 391), only one-shot deviations need be checked to ensure subgame perfection, where a one-shot deviation from a strategy consists of a single period deviation followed by sticking to the strategy afterwards.…”
Section: De…nitionmentioning
confidence: 94%
“…Simple strategy pro…les are de…ned to avoid single player deviations (Abreu (1988)). Deviations of two or more players are always ignored.…”
Section: Quasi Even Stronger Perfect Equilibriummentioning
confidence: 99%
“…In Section 4, we discuss the case where upstream firms cannot exclude any unrelated buyer. 6 Although this punishment strategy is not optimal (Abreu, 1988), we use it for simplicity and tractability. Indeed many previous studies have adopted the grim trigger strategy when analyzing stability of agreements.…”
Section: The Modelmentioning
confidence: 99%
“…These twin roles of transfer pricing have been the focus of much research. 1 When some divisions of a firm face competition, research has further shown that transfer prices can also serve strategic purposes (Alles and Datar, 1998;Zhao, 2000;Arya and Mittendorf, 2008). Typical reasoning for the strategic use of transfer pricing relies on the firm's ability to exercise price discrimination: by charging transfer price to its own affiliate that is different from what the firm would charge unrelated buyers, the firm is able to improve the affiliate's competitive posture against the unrelated competitors.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of punishment strategies and the determination of the optimal punishment scheme (Abreu [1988]) will be investigated in further works. This is true when p → 0, i.e.…”
Section: Notesmentioning
confidence: 99%